Ternary cyclodextrin polyurethanes containing phosphate groups: Synthesis and complexation of ciprofloxacin. (20th October 2016) - Moreira, Mirna Pereira; Andrade, George Ricardo Santana; de Araujo, Marcia Valeria Gaspar; Kubota, Tatiana; Gimenez, Iara F.
Highlights: Synthesis of ternary cyclodextrin polyurethanes was studied. Plyurethanes were formed from HDI, β-glicerophosphate and β-cyclodextrin. Inclusion complexes with ciprofloxacin were studied. Abstract: Synthesis of ternary polyurethanes (PUs) from hexamethylenediisocyanate, β-cyclodextrin and β-glycerophosphate (acid and calcium salt) was studies varying synthesis parameters such as monomer proportion, heating method (reflux and microwave), and catalyst amount. Favorable conditions were provided by microwave irradiation and use of β-glycerophosphoric acid although the results suggest that it is possible to obtain ternary PUs with the calcium salt. FTIR data indicated the existence of secondary urea linkages. After characterization of ternary PUs by FTIR spectroscopy, XRD and thermal analysis, as well as evidences that the cyclodextrin cavities remained active toward inclusion of guest molecules, the possibility of inclusion of the antibiotic ciprofloxacin was evaluated. Absence of ciprofloxacin melting peak in DSC curves indicated that it is molecularly dispersed within the polymer, possibly included in the cyclodextrin. In vitro release experiments suggested additional non-inclusion interactions, showing also that the use of dialysis membranes may mask the actual release profile.